Dampak Kebijakan Tarif PDAM Tirtanadi Terhadap Kepuasan Pelanggan : Studi Kasus PDAM Tirtanadi Cabang Medan Denai - Maulana Aksan; Marliyah Marliyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PDAM tariffs and policies have a very important role in maintaining the availability of clean water and quality services for the community. Economically, the tariffs set by PDAM enable the provision of clean water in a sustainable manner with operational finance, infrastructure maintenance, and investment in developing the water distribution network. This research aims to reveal the impact of PDAM Tirtanadi's tariff adjustment policy on customer satisfaction. Adjusting air tariffs is an important step for PDAMs to finance infrastructure maintenance and operations, but this can also have an impact on customer satisfaction. The research method used is qualitative research with a descriptive approach. Qualitative research makes it possible to describe phenomena in depth, including the impact of PDAM Tirtanadi's tariff policy on customer satisfaction. In the descriptive method, the main focus is on a detailed and in-depth description of the observed phenomenon, without carrying out statistical analysis. The data used in this research comes from writings contained in books, scientific journals, previous research and through interviews with customers and related parties of PDAM Tirtanadi Medan Denai Branch during college internships. The results of this research indicate that the tariff adjustment policy creates hopes and concerns among customers, who hope that service quality will increase in line with tariff increases. In addition, this research also identifies factors that influence customer perceptions of tariff policies, including the quality of services provided, transparency in the use of funds, and responsiveness to customer complaints. The implications of this research are the importance of considering customer needs and expectations in designing adequate tariff policies, as well as the importance of transparency and accountability in providing public services such as the provision of drinking water.